P104 Computed tomography evidence of lymphangitis associated to malignant pleural effusion: its prevalence and impact on survival. (12th November 2019) - Castro-Anon, O; Dudina, A; George, V; Mercer, R; McCracken, D; Asciak, R; Hassan, M; Hallifax, R; Russel, N; Rodriguez-Panadero, F; Rahman, N
Abstract : Introduction: For the treatment of malignant pleural effusion (MPE), it is relevant to know prognosis in order to determine the best treatment approach. The general prognosis of patients with lymphangitic carcinomatosis is poor. The prevalence and prognosis of lymphangitis in patients diagnosed with MPE is not known. Objectives: To determine the prevalence of computed tomographic (CT) lymphangitis in patients diagnosed with symptomatic MPE and to assess prognosis. Secondary objective: to evaluate other radiological findings such as trapped lung, thoracic lymphadenopathy, pulmonary nodules, pleural thickening, pleural nodules and pericardial effusion. Methods: This is an observational, retrospective, single-centre study of consecutive patients diagnosed with MPE, between January 2015 and December 2017; the chest CTs were reported by thoracic radiologists. Follow-up occurred until death or at least one year. Results: 298 patients diagnosed with MPE were included (mean age 72; 50.7% women). The LENT score was low in 15.7% cases, moderate in 62.2% and high in 22.1%. Lymphangitis was identified in 10.4% of the cases: 51.6% ipsilateral, 12.9% contralateral and 29% bilateral; its prevalence was higher in patients with lung cancer and breast cancer (19.4%). Other abnormal chest CT findings were noted in 93.9%: 54.4% thoracic lymphadenopathy, 52.5% pulmonary nodules, 48.5% pleural thickening, 35, 8% pleural nodularity, 21.4% trapped lung, 18.5% lung mass, 12.5% emphysema and 9.1% pericardial effusion. 250 patients (85.9%) died: 29 with lymphangitis (93.5%) and 221 without lymphangitis (85%). Lymphangitis was associated with a higher mortality within one month after diagnosis (p=0.036) but it was not after 3 months (p=0.073), 6 months (p=0.230) and one year (p=0.196). The presence of thoracic lymphadenopathy (p=0.030) and pulmonary nodules (p=0.004) had an increased risk of mortality. Conclusions: Lymphangitis accounted for approximately 10% of patients with MPE and it was associated with poor survival only within one month. Other abnormal chest CT findings were noticed frequently; those patients with thoracic lymphadenopathy and pulmonary nodules had poor prognosis. Prospective studies are needed to confirm the impact on survival of lymphangitis in patients with MPE. Acknowledge: European Respiratory Society (ERS CTF201804–00345).